1997
DOI: 10.1001/archinte.1997.00440340047004
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Dying of End-Stage Liver Disease

Abstract: It is difficult to estimate the total cost of ESLD; however, in evaluating inpatient costs, we see that it is expensive and significant amounts are spent on patients who die. Further study is necessary to determine which factors can optimize the cost of ESLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…For example, in this analysis, liver transplantation cost $108659 for the first year and $18976 per year subsequently (in 1999 dollars), but other studies that used charge data reported transplantation costs of $200 000 or higher for the surgery and $25000 per year for medications. 57,58 In addition to direct medical costs, our analysis suggested that the societal burden of indirect or time costs 59 related to premature mortality or disability from decompensated cirrhosis or hepatocellular carcinoma may add another $54.2 and $21.3 billion, respectively, in lost productivity, both of which exceed the $10.3 billion baseline direct medical costs of hepatitis C.…”
Section: Discussionmentioning
confidence: 90%
“…For example, in this analysis, liver transplantation cost $108659 for the first year and $18976 per year subsequently (in 1999 dollars), but other studies that used charge data reported transplantation costs of $200 000 or higher for the surgery and $25000 per year for medications. 57,58 In addition to direct medical costs, our analysis suggested that the societal burden of indirect or time costs 59 related to premature mortality or disability from decompensated cirrhosis or hepatocellular carcinoma may add another $54.2 and $21.3 billion, respectively, in lost productivity, both of which exceed the $10.3 billion baseline direct medical costs of hepatitis C.…”
Section: Discussionmentioning
confidence: 90%
“…This is particularly relevant in cirrhotic patients, owing to the exponential increase in the incidence of this condition and the limited ICU resources (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Our study assessed, to our knowledge for the first time, the accuracy of prognostic scores in cirrhotic patients admitted to a GICU. In our series, all the tested scores displayed good discrimination and calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant percentage (36.7%) of the total cost of ICU care for cirrhotic patients is spent on those who do not survive (11,16,19). Additionally, it must be borne in mind that ICUs are a very limited health resource (10,11,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] For infected individuals who either fail treatment or go untreated, the suffering and cost of end-stage liver disease can be enormous. 31 …”
Section: Discussionmentioning
confidence: 99%